Small scale DNA preps for Neurospora crassa - J. Irelan; V. Miao; E. U. Selker (Fungal Genetics Reports, 1993)
Molecular biology experiments often require preparation of small amounts of DNA from many samples. This abbreviated DNA isolation method yields an average of 0.6 micrograms of genomic DNA that is suitable for Southern analysis or PCR. Starting with fresh mycelium, 20 to 40 samples can be processed in approximately two hours. Better yields (about 5 micrograms) may be obtained by suspending approximately 100 microliters of ground lyophilized mycelium in 500 microliters of isolation buffer and following the protocol starting from step 4. "Spin" refers to centrifugation of samples at 14,000 rpm in a microcentrifuge.